Brain-Derived Neurotropic Factor, Vascular Endothelial Growth Factor and Matrix Metalloproteinases as Markers of Metabolic Status in Non-Growth Hormone-Treated Girls With Turner Syndrome - Błaszczyk, Ewa; Gawlik, Jakub; Gieburowska, Joanna; Tokarska, Agnieszka; Kimsa-Furdzik, Małgorzata; Hibner, Grzegorz; Francuz, Tomasz; Gawlik, Aneta Monika (Frontiers in Endocrinology, 2021)
Background. Turner syndrome (TS) presents a high risk of congenital heart defects and may predispose to both obesity and related metabolic complications. Hence the search for new markers as potential early predictors of the metabolic syndrome (MetS) and cardiovascular diseases appears warranted. Objective. To assess MMP-1 (matrix metalloproteinase-1), MMP-2 (matrix metalloproteinase-2), MMP-9 (matrix metallopeptidase-9), BDNF (brain-derived neurotrophic factor), GDNF (glial cell line-derived neurotrophic factor), and VEGF (vascular endothelial growth factor) in non-MetS TS girls not treated with growth hormone (GH) vs. healthy short stature girls, and to assess the connection with basic metabolic parameters. Method. The concentrations of circulating MMP-1,2,9, BDNF, GDNF and VEGF were measured in 12 patients with TS not treated with growth hormone. The control group was composed of 17 girls with non-pathologic short stature. The patients’ clinical and biochemical phenotypes were determined by weight, height, total cholesterol, HDL cholesterol, triglycerides, glucose, aminotransferases, IGF1, TSH and fT4. Results. There were no differences in mean age, weight, BMI Z-Score or hSDS between groups; however, they differed in baseline values of ALT (18.2 ± 4.2 vs. 14.2 ± 4.1, p= 0.02), BDNF [29951.5 (26176.9 – 41271.9) vs. 23131.7 (18392.4 – 28313.3), p=0.01] and MMP-2 [91.8 (71.7 – 111.0) vs. 143.6 (123.7 - 244.5), p< 0.001]. BDNF correlated with ALT activity (r = 0.56 p = 0.002) and BMI Z-score (r = 0.38 p = 0.042), while MMP-2 correlated with HDL concentration (r = 0.48 p = 0.029) in all the patients. The analysis of the study group alone revealed significant positive correlations between MMP-9 and TSH (r = 0.74 p = 0.036), BDNF and both ALT (r = 0.73 p = 0.038) and TSH (r = 0.85 p = 0.008), and a negative correlation between MMP-1 and fT4 (r = -0.75 p = 0.032). The control group did not present any significant correlations. Conclusion. The higher concentrations of BDNF and lower of MMP-2 found in girls with TS without MetS compared to healthy girls with short stature, could have a major impact on the future “natural” development of the metabolic status. Our findings need further studies.